Adsorption Study of Some Sulphanilic Azo Dyes on Charcoal - H. J. Mohammed; B. J. Kadhim; Aseel Sh. Mohammed (E-Journal of Chemistry)
Studies on the removal of two dyes (sulphanilic azo antipyrine and sulphanilic azo imidazole) from aqueous solution by adsorption on charcoal as an adsorbent were carried out. A series of experiments were under taken in a batch adsorption technique to access the effect of the process variables i.e. contact time, initial dye concentration, initial pH, adsorbent dose and temperature. Adsorbent dosage (0.1 g) higher value for both dyes. The equilibrium in the solution was observed within (35 min) of two sulphanilic dyes on charcoal. The equilibrium isotherms for both dyes were determined to describe the adsorption process. The results showed that the equilibrium data was fitted by of the Freundlich isotherms on charcoal surface. The result obtained shows that the adsorption isotherm for both dyes on charcoal was according to Giles classification. The thermodynamic factors such as ∆Η, ∆G and ∆S were calculated.